Flipbook tematik: Alternatif media pembelajaran PKN berbasis fliphtml5 di SD - Delfita Nur Aprilutfi (ARKA INSTITUTE, 2022)
Education is the process of preparing students to pursue their goals in the future. Online learning is a type of education that incorporates technology into the learning process. Flipbook media on theme learning is one of the techniques to promote online learning. Flipbook is a digital sheet with educational resources, videos, and instructional images that explain students' learning. This thematic flipbook is suitable for PKN learning. Learners who have a sense of nationalism, patriotism, love of the sublime homeland, open mind, independence, and creativity for the country and nation are formed through pkn learning in elementary school. This research aims to create a thematic flipbook for grade IV students with Fliphtml5-based PKN learning. This research is qualitative research. This qualitative research is used to explain the thematic flipbook topics based on fliphtml5 as a medium means for fourth graders to learn PKN.